Hypertension Among Elderly in Slum: A Neglected Issue - Govindasamy, Venkatesh; Hiremath, Ravishekar N; Kohli, Sarvesh; Bhatti, Vijay Kumar; Kumar, Raj; Mahen, Ajoy (National Journal of Community Medicine, 2013)
Introduction: Hypertension is an important public health problem worldwide. Hypertensive has higher risk of developing coronary artery disease; cerebrovascular disease and stroke. Objectives: The objective was to study the prevalence of hypertension and its associated risk factors and awareness regarding hypertension in urban slum Materials and methods: A Cross Sectional study was carried out amongst people with age 60 years in an urban slum of Pune. Total 125 subjects, selected by Systematic random sampling, were interviewed for data collection by means of pre tested questionnaire and blood pressure of study subjects was measured by mercury sphygmomanometer. Results: The mean age of the study participants was 64.93(+ 5), 32% were male and 27% were illiterate. The prevalence of hypertension among elderly people was 55%, out of which 21% were unaware of their hypertensive status. BMI >25 was associated with hypertensive’s (OR 2.4 (1.1-5.04)). However, variables like sex, alcohol, tobacco were not associated with hypertension. Awareness among study subjects was very low. Conclusion: One in every two elderly persons is suffering from high blood pressure and is unaware of their status. Primary prevention towards younger population and secondary & tertiary prevention towards elderly should be fastened. At the same time awareness campaign should be carried out particularly for slum target population.